Development of Directly Recycled AA6061 Aluminium Composite Reinforced with Graphite Using Casting (Foundry) Method - Rosdi, Hamzah Luqman; Mohamed Hatta, Mohamed Nasrul (Research Progress in Mechanical and Manufacturing Engineering, 2026)
Aluminum alloy AA6061 is widely used in engineering applications due to its favorable strength-to-weight ratio, corrosion resistance, and good machinability. With an increasing emphasis on sustainability and energy efficiency, secondary recycling of aluminum has become a crucial alternative to primary production, which is highly energy-consuming. This study investigates the development of directly recycled AA6061 aluminum composites reinforced with graphite using a casting (foundry) method. Recycled AA6061 chips were reinforced with different graphite volume fractions (5%, 10%, and 12.5%) and fabricated through controlled casting conditions. The mechanical and physical properties of the composites were evaluated through tensile testing, Vickers microhardness measurements, and density analysis. Microstructural characteristics were examined using optical microscopy, scanning electron microscopy (SEM), and energy-dispersive spectroscopy (EDS). The results indicate that incorporating graphite improves microhardness and reduces density, thereby contributing to the lightweight characteristics of the material. An optimum graphite content was observed to enhance tensile strength, whereas excessive graphite addition led to particle agglomeration, increased porosity, and weakened interfacial bonding. Microstructural analysis confirmed grain refinement and successful incorporation of graphite within the aluminum matrix. Overall, the findings demonstrate that graphite-reinforced recycled AA6061 composites produced via casting offer a promising and sustainable approach for lightweight engineering applications, provided that the reinforcement content and processing parameters are carefully optimized